Fit for purpose? Evaluating climate change adaptation laws and policies for marine aquaculture in Chile - Engler, Cecilia (Frontiers in Marine Science, 2024)
This research article describes Chile’s climate change adaptation policies and plans for marine aquaculture in Chile, with a focus on the nationally important salmon farming industry, and assesses whether they have adequately addressed legal barriers to adaptation and the need for legal transformation. The article first outlines Chile’s climate change law, policies, and institutional framework, as reflected in the 2022 Framework Act on Climate Change, the 2020 updated Nationally Determined Contribution, the 2022 Strengthening of the Nationally Determined Contribution, and the 2022 Long-Term Climate Strategy. The article highlights the special attention given to the ocean-climate nexus in both international and national policy agendas. It then summarizes and assesses the adaptation policies and plans for the aquaculture sector. Three main shortcomings are identified: the lack of implementation of committed activities, the lack of a strategic vision for the role of aquaculture in a changing climate and oceans, and the lack of attention to the limits of adaptation resulting from existing regulatory frameworks. The article then strengthens this assessment with a legal analysis of the adaptive capacity of aquaculture planning and leasing frameworks. This assessment concludes that mainstreaming climate change into existing planning instruments is an ineffective adaptation measure due to the fragmented, rigid, and inefficient legal framework for the planning of aquaculture and other uses of the coastal zone. In turn, the leasing system is too rigid to allow for effective adaptation. Various mechanisms to introduce flexibility are suggested. The article concludes by highlighting an unprecedented window of opportunity to advance strategic, coherent, long-term, and transformative adaptation, resulting from concurrent initiatives to reform or update aquaculture law, policy, and adaptation planning and the principled approach to climate action embedded in the Framework Act on Climate Change.